International Care Bundle Evaluation in Cerebral Hemorrhage Research (I-CATCHER) : Study protocol for a multicenter, batched, parallel, cluster-randomized trial with a baseline period - Apostolaki-Hansson, Trine ; 0000-0003-4063-5476; Ouyang, Menglu; Dowlatshahi, Dar; Caso, Valeria; Bufi, Alessandro; Law, Zhe Kang; Billot, Laurent; Norrving, Bo; Anderson, Craig S.; Ullberg, Teresa (International Journal of Stroke, 2025)
Rationale: A care bundle approach to the management of spontaneous intracerebral hemorrhage (ICH) has been shown to benefit patients in low- and middle-income countries (LMIC), but uncertainty persists over the specific components and its applicability in high-income countries (HICs). Aims: An international collaborative initiative aimed at determining whether implementation of a care bundle improves functional outcome for patients with ICH in HIC. Methods: An international, multicenter, batched, parallel, cluster-randomized clinical trial focused on implementation and quality improvement for adults with spontaneous ICH ⩽24 h of symptom onset. The care bundle includes time- and target-based interventions: early intensive blood pressure lowering, hyperglycemia and pyrexia management, anticoagulation reversal, avoidance of do-not-resuscitate orders, repeat imaging, and referral pathways for intensive care and neurosurgery. An embedded process evaluation will assess the effectiveness and implementation of the care bundle. Sample size: A total of 110 hospitals with 3500 ICH participants is estimated to provide 90% power (α = 0.05) to detect a plausible treatment effect of 0.20 improvement in utility-weighted modified Rankin scale (UW-mRS) scores. Outcomes: The primary outcome is UW-mRS at 6 months. Secondary outcomes include death, functional status, and health-related quality of life. Implementation outcomes include adoption, fidelity, acceptability, sustainability, and integration. Discussion: We aim to provide reliable evidence to accelerate practice change for integration of a multifaceted ICH care bundle as a critical component of acute stroke care worldwide. Trial registration: Clinicaltrials.gov Identifier: NCT06429332.
Publisher Copyright: © 2025 World Stroke Organization. This article is distributed under the terms of the Creative Commons Attribution 4.0 License (https://creativecommons.org/licenses/by/4.0/) which permits any use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access page (https://us.sagepub.com/en-us/nam/open-access-at-sage).
Keywords: blood pressure lowering; care bundle; cluster trial; implementation; Intracerebral hemorrhage; outcome